Fixed and in flux: the identity of a hospitality degree program at a Canadian community college. (2nd January 2023) - Weaver, Adam; Clark, Heather
ABSTRACT: This paper applies the concept of identity – typically associated with individuals and self-definition – to the study of a degree program, a collective educational enterprise. Faculty members and senior administrators at a community college in Canada with ties to the development of a hospitality degree program were interviewed. This paper examines identity within a different empirical and scalar context (a degree program rather than individuals) and in a manner that is different conceptually (addressing the idea that identity has both enduring and changing features). The competitive academic marketplace has shaped the identity of the hospitality degree program at Niagara College Canada. Commercial pressures, themselves fixed and in flux, have driven the formation of an identity that has attributes that are fixed and in flux. The notion of identity is interwoven with business imperatives and may offer guidance to hospitality degree programs in the context of a post-pandemic economic recovery.